PENGARUH FREE CASH FLOW, FINANCIAL DISTRESS, DAN EMPLOYEE DIFF TERHADAP MANAJEMEN LABA - Nisa Nazalia; Dedik Nur Triyanto (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2018)
This study aims to understand Free Cash Flow, Financial Distress, Employee Diff, and Earnings Management on object research and also examine the effect simultaneously and partially between Free Cash Flow, Financial Distress, and Employee Diff to Earnings Management. The population in this study refers to the mining companies that listed in Indonesia Stock Exchange period 2012-2016. The techniques used in this study is purposive sampling with 34 samples of the companies were selected which in the period of five years, so there were 170 samples data of companies listed in Indonesia Stock Exchange perios 2012-2016 are used. Methods of data analysis in this research is panel data regression analysis using Eviews 10. Based on the result of this research shows that simultaneously Free Cash Flow, Financial Distress, and Employee Diff have a significant effect on Earnings Management. Partially, Free Cash Flow has no effect on Earnings Management, while Financial Distress and Employee Diff have a positive and significant effect on Earnings Management.